'A Berlin psychiatrist with an American passport': Lothar Kalinowsky, electroconvulsive therapy and international exchange in the mid-twentieth century. Issue 4 (December 2015) - Rzesnitzek, Lara
The emigration of Lothar Kalinowsky (1899–1992) might, at first glance, seem to be a history of coincidence and twists of fate, but it is shown to be a truly entangled and intertwined history and story. The international introduction of electroconvulsive therapy was not only closely involved with the political, scientific and economic conditions during World War II, but the story of Kalinowsky's relevance to it emerges from competing stories, told differently in Europe and the USA – and by Kalinowsky himself. Tracing these stories up to the end of the 1960s reveals Kalinowsky as an influential inheritor and patron of Berlin Biological Psychiatry, rather than telling the history of an émigré innovator of international neuropsychiatric research.